A boundless God: the Spirit according to the Old Testament - Levison, John R. (Baker Academic, a division of Baker Publishing Group, 2020)
Spirit blowing and breathing -- Spirit coming upon -- Spirit resting upon -- Spirit passed on -- Spirit poured out -- Spirit filling -- Spirit cleansing -- Spirit standing and guiding.